"The most patient of animals, next to the ass:" Jan Smuts, Howard University, and African American Leadership, 1930. Issue 1 (2nd January 2017) - Edgar, Robert; Houser, Myra Ann
Abstract: Former South African Prime Minister Jan Smuts's 1930 European and North American tour included a series of interactions with diasporic African and African American activists and intelligentsia. Among Smuts's many remarks stands a particular speech he delivered in New York City, when he called Africans "the most patient of all animals, next to the ass." Naturally, this and other comments touched off a firestorm of controversy surrounding Smuts, his visit, and segregationist South Africa's laws. Utilizing news coverage, correspondence, and recollections of the trip, this article uses his visit as a lens into both African American relations with Africa and white American foundation work toward the continent and, especially, South Africa. It argues that the 1930 visit represents an early example of black internationalism and solidarity, reflecting a shift from sociocultural connections between Africa and the diaspora to creating political movements on behalf of African people. To contextualize this visit, we assess events surrounding a meeting that the Phelps-Stokes Fund organized for Smuts at Howard University, using this as a lens into the two disparate, yet interlocked, communities.